The SAR of brain penetration for a series of heteroaryl urea FAAH inhibitors. Issue 13 (1st July 2016) - Keith, John M.; Tichenor, Mark S.; Apodaca, Richard L.; Xiao, Wei; Jones, William M.; Seierstad, Mark; Pierce, Joan M.; Palmer, James A.; Webb, Michael; Karbarz, Mark J.; Scott, Brian P.; Wilson, Sandy J.; et al.
Graphical abstract: The SAR of brain penetration for a series of heteroaryl piperazinyl- and piperadinyl-urea fatty acid amide hydrolase (FAAH) inhibitors is described. Brain/plasma (B/P) ratios ranging from >4:1 to as low as 0.02:1 were obtained through relatively simple structural changes to various regions of the heteroaryl urea scaffold. It was not possible to predict the degree of central nervous system (CNS) penetration from the volumes of distribution ( V d ) obtained from PK experiments as very high V d s did not correlate with high B/P ratios. Similarly, calculated topological polar surface areas (TPSAs) did not consistently correlate with the degree of brain penetration. The lowest B/P ratios were observed for those compounds that were significantly ionized at physiological pH. However, as this class of compounds inhibits the FAAH enzyme through covalent modification, low B/P ratios did not preclude effective central target engagement. Abstract: The SAR of brain penetration for a series of heteroaryl piperazinyl- and piperadinyl-urea fatty acid amide hydrolase (FAAH) inhibitors is described. Brain/plasma (B/P) ratios ranging from >4:1 to as low as 0.02:1 were obtained through relatively simple structural changes to various regions of the heteroaryl urea scaffold. It was not possible to predict the degree of central nervous system (CNS) penetration from the volumes of distribution ( V d ) obtained from pharmacokinetic (PK) experiments as very high V d s did not correlate with high B/P ratios. Similarly, calculated topological polar surface areas (TPSAs) did not consistently correlate with the degree of brain penetration. The lowest B/P ratios were observed for those compounds that were significantly ionized at physiological pH. However, as this class of compounds inhibits the FAAH enzyme through covalent modification, low B/P ratios did not preclude effective central target engagement.